Improving the energy-efficiency of buildings: the impact of environmental policy on technological innovation - Joëlle Noailly (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper investigates the impact of alternative environmental policy instruments on technological innovations aiming to improve energy-efficiency in buildings. The empirical analysis focuses on three main types of policy instruments, namely regulatory energy standards in buildings codes, energy taxes as captured by energy prices and specific governmental energy R&D expenditures. Technological innovation is measured using patent counts for specific technologies related to energy-efficiency in buildings (e.g. insulation, high-efficiency boilers, energy-saving lightings). The estimates for seven European countries over the 1989-2004 period imply that a strengthening of 10% of the minimum insulation standards for walls would increase the likelihood to file additional patents by about 3%. In contrast, energy prices have no significant effect on the likelihood to patent. Governmental energy R&D support has a small positive significant effect on patenting activities.
Keywords: O31; O34; Q55; 330; Innovation; Technological Change; Patents; Energy-Efficiency; Buildings; Environmental Policy